2022
DOI: 10.3390/curroncol29050272
|View full text |Cite
|
Sign up to set email alerts
|

Framing Concerns about Body Image during Pre- and Post-Surgical Consultations for Head and Neck Cancer: A Qualitative Study of Patient–Physician Interactions

Abstract: Patients with head and neck cancer report high unmet psychosocial needs as they undergo lifesaving treatments that can significantly alter their appearance and cause functional impairments. This qualitative analysis of recordings of 88 pre- and post-surgical consultations involving 20 patients respond to the need for empirical studies of patient–provider conversations about body image concerns. It indicates that the emphasis on concerns about survival, cure, and physical recovery during clinical consultations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
1
0
0
Order By: Relevance
“…Previous qualitative investigations reported the profound biopsychosocial impact of HNC and its management on patient’s quality of life 23 24. Our results supported earlier qualitative work with this population18 and found that ND does not always, but can, have a large negative impact on the patient’s physical and mental functioning which decreases a patient’s quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…Previous qualitative investigations reported the profound biopsychosocial impact of HNC and its management on patient’s quality of life 23 24. Our results supported earlier qualitative work with this population18 and found that ND does not always, but can, have a large negative impact on the patient’s physical and mental functioning which decreases a patient’s quality of life.…”
Section: Discussionsupporting
confidence: 89%